Pharmacokinetic study of Piperine in Wistar rats after oral and intravenous administration - Promod Kumar Sahu; Anjna Sharma; Sheikh Rayees; Gurleen Kour; Amarinder Singh; Mowkshi Khullar; Asmita Magotra; Shravan Kumar Paswan; Mehak Gupta; Ishtiyaq Ahmad; Sumit Roy; Manoj Kumar Tikoo; et al. (International Journal of Drug Delivery, 2014)
To evaluate the potential of piperine as a therapeutic agent, we considered whole animal studies to characterize its pharmacokinetics (PK) in Wistar rats after oral and intravenous (i.v.) administration, using high performance liquid chromatography (HPLC). This study will enable in determination of piperine exposures needed to predict the dose regimen for clinical trials to test the proposed mechanism of action in enhancing the therapeutic efficacy of the concurrently administered drugs. A single dose of piperine was administered intravenously (10 mg/kg) by jugular vein cannulation and orally (20 mg/kg) by oral gavage in male Wistar rats. Serial blood samples were collected and plasma piperine concentrations were determined using HPLC. After intravenous administration the apparent terminal half-life (7.999 hr), apparent steady state volume of distribution (7.046 L/kg) and total body clearance (0.642 L/kg/hr) were calculated. After oral administration the apparent terminal half-life (1.224 hr), apparent steady state volume of distribution (4.692 L/kg) and total body clearance (2.656 L/kg/hr) were calculated. The peak plasma concentration of piperine in plasma after oral administration was found to be 0.983 μg/ml, occurred approximately 2 hr post-dose. The AUC(0-∞) of Piperine after oral and intravenous administration in rats were found out to be 7.53 μg*hr/ml and 15.6 μg*hr/ml, respectively. The absolute oral bioavailability of piperine was found to be 24%. From the results of the experiment, it can be concluded that piperine achieves extensive distribution because of its large volume of distribution in the body. These studies are useful in interpreting preclinical efficacy studies of Piperine & predicting human pharmacokinetic through scaling technique.